OPTIMALISASI KESEHATAN OTAK IBU HAMIL MELALUI POLA HIDUP SEHAT PENDEKATAN INTERPROFESSIONAL COLLABORATION - Hutagaol, Rutmauli; Hipni, Rubiati; Fauziah, Erna; Pratiwi, Niken (UPPM Poltekkes Kemenkes Banjarmasin, 2024)
The brain health of pregnant women is an important aspect that affects maternal well-being and fetal development. Knowledge about health checks, including BSE (Breast Self-Examination), and the implementation of a healthy lifestyle during pregnancy play a major role in maintaining the brain health of pregnant women. This community service aims to optimize the brain health of pregnant women through BSE education and the implementation of a healthy lifestyle with the Interprofessional Collaboration (IPC) approach in the Assisted Village of the Tambarangan Health Center Area, Tapin Regency. The results showed that most pregnant women were aged 25-35 years (60.0%) and had little knowledge about BSE (60.0%). More worryingly, all pregnant women (100%) had never performed BSE. This low level of knowledge not only increases the risk of late detection of breast cancer, but can also trigger stress and anxiety that have a negative impact on the mental and brain health of pregnant women. Through the IPC approach, integrated education from various health professions (doctors, nurses, midwives, nutritionists, and psychologists) is carried out to improve the knowledge of pregnant women about BSE, stress management, and the implementation of a healthy lifestyle. This program helps pregnant women understand the importance of maintaining brain health by paying attention to nutritional intake, physical activity, and routine check-ups. This interprofessional collaboration plays an important role in integrating comprehensive promotive and preventive efforts, so that it can reduce the risk of physical and mental complications in pregnant women. These findings emphasize the importance of ongoing education and a holistic approach to improving the well-being of pregnant women in rural communities.